Implementation of Virtual Reality in Simple Math Quizzes as Children's Learning Platform - Muchammad Danief Zulfa Ridloka; Vivy Cahyani; Hatta Zuama Bintang Aulia; M. Mahaputra Hidayat (JEECS (Journal of Electrical Engineering and Computer Sciences), 2023)
This research focuses on the implementation of virtual reality (VR) in simple math quizzes as a children's learning platform. The background of this research stems from the need for innovative and engaging educational tools to enhance children's learning experiences in mathematics. Traditional methods of teaching mathematics often lack interactivity and fail to captivate young learners. By leveraging the immersive and interactive nature of VR technology, this research aims to address these challenges and create an effective learning platform for children. The main problem addressed by the research is the difficulty children often face in grasping mathematical concepts due to their abstract nature. By integrating VR into math quizzes, children can visualize and manipulate mathematical concepts in a virtual environment, fostering a deeper understanding of the subject matter. Additionally, the use of VR can make learning math more enjoyable and engaging for children, leading to increased motivation and improved learning outcomes. The research utilizes a specific model of VR technology to implement the app math quizzes. The exact model used is not specified in the abstract. However, it can be assumed that the chosen VR hardware and software align with the requirements of creating an interactive and immersive learning experience for children. The VR technology allows for the creation of virtual environments where children can interact with mathematical elements and solve quizzes in an engaging manner. In terms of the software development life cycle (SDLC) and design pattern method used in this research, no specific information is provided in the abstract. Further details are required to determine the specific SDLC and design pattern method employed in the implementation of the VR-based math quizzes.